The interpretation of some Conopidae (Diptera) described by Robineau-Desvoidy - Stuke, Jens-Hermann; Clements, David K. (Zootaxa, 2005)
Conopidae material determined by Robineau-Desvoidy and held in the Hope Department of the University Museum, Oxford (UMO) has been examined. As a result, lectotypes for 13 of the species described by Robineau-Desvoidy can be designated, and the following new synonymies are proposed [syn. nov.]: Myopa nana Robineau-Desvoidy, 1830 = Myopa occulta Wiedemann in Meigen, 1824; Myopa pellucida Robineau-Desvoidy, 1830 = Myopa fulvipalpis Robineau-Desvoidy, 1853 = Myopa extricata Collin, 1960; Myopella florea Robineau-Desvoidy, 1853 = Myopa buccata (Linnaeus, 1758); Occemya nitidula Robineau-Desvoidy, 1853 = Zodion carceli RobineauDesvoidy, 1853 = Zodion cinereum (Fabricius, 1794); Purpurella nobilis Robineau-Desvoidy, 1853 = Myopa dorsalis Fabricius, 1794. Type species are fixed for the 11 conopid genera described by Robineau-Desvoidy in accordance with Article 70.3.1 of the ICZN. It is proposed to interpret Zodion kroeberi Szilády, 1926 as a valid species [stat. rev.] and to introduce this as the valid name for Zodion carceli auct.